1992
DOI: 10.1111/j.1432-1033.1992.tb17474.x
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of the degradation of non‐enzymatically glycated proteins under physiological conditions

Abstract: The degradation of fructosamines, formed from the non-enzymic glycation of proteins under physiological conditions, to advanced glycation end products was investigated by studying the model peptide fructosamine NE-(1-deoxy-D-fructos-1-y1)hippuryl-lysine (DHL). At pH 7.4 and 37°C in aerobic phosphate buffer, DHL degraded to form N,-carboxymethyl-hippuryl-lysine, and hippuryllysine over a 29-day incubation period. The expected NE-(3-1actato)hippuryl-lysine and 'hippuryllysylpyrraline' derivatives were not found.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(77 citation statements)
references
References 39 publications
0
77
0
Order By: Relevance
“…Although the experiments presented above and by others (12,33,35,36) implicate Amadori products in the formation of H 2 O 2 in vitro, several questions arise concerning the mechanism and source of H 2 O 2 formation in vivo with relationship to the Maillard reaction. Current concepts linking H 2 O 2 formation from reducing sugars involve metal-catalyzed oxidation of enediols (27,33).…”
Section: Discussionmentioning
confidence: 80%
See 1 more Smart Citation
“…Although the experiments presented above and by others (12,33,35,36) implicate Amadori products in the formation of H 2 O 2 in vitro, several questions arise concerning the mechanism and source of H 2 O 2 formation in vivo with relationship to the Maillard reaction. Current concepts linking H 2 O 2 formation from reducing sugars involve metal-catalyzed oxidation of enediols (27,33).…”
Section: Discussionmentioning
confidence: 80%
“…A highly effective diminution of TBT increase was noted with native but not with heatinactivated catalase, thereby implicating H 2 O 2 in the Amadori product-mediated increase in heat stability of the tendons. CML was not determined in this experiment because two groups have shown unequivocally that catalase suppresses CML formation (35,36). Although these data implicate H 2 O 2 in cross-linking of collagen exposed to Amadori product in vitro, the role of H 2 O 2 for collagen cross-linking in vivo remained to be established.…”
Section: Resultsmentioning
confidence: 97%
“…Glycation of proteins in CRF and ESRD is expected to increase because of increased concentrations of ␣-oxoaldehyde glycating agents (9,10,27). The concentration of FL residues may be decreased in CRF and HD patients by increased oxidative stress with conversion of FL to CML residues (15). High levels of glycoxidation adducts (pentosidine and CML) in HD may reflect increased oxidative stress, relative to PD (29).…”
Section: Discussionmentioning
confidence: 99%
“…This was decreased to 0.34 mmol/mol lys (Ϫ59%) in CRF patients and to 0.39 mmol/mol lys (Ϫ53%) in HD patients but was not decreased significantly in PD patients (Figure 6a). FL residues degrade to form CML residues (15). The plasma protein content of CML residues was 0.039 mmol/mol lys in control subjects and increased two-fold in CRF and PD patients and three-fold in HD patients.…”
Section: Glycation Oxidation and Nitration Adduct Residues In Plasmmentioning
confidence: 93%
“…CML-human serum albumin (HSA) and CML-BSA were prepared as described previously. 19,20) Amino acid analysis 18) indicated that CML contents of CML-HSA prepared were 18.01 mol CML per mol HSA.…”
Section: Overproduction Of N E E -(Carboxymethyl)lysine-induced Neovamentioning
confidence: 99%